soils Research the possibility of stabilization some weak using tile waste - حسون, صبا; رامي حنا (Latakia University Journal -Engineering Sciences Series, 2023)
The researchers treated the stabilization of weak soils with additions, the most important of which are the fixation with all kinds of lime and Portland cement. And with the end of the last century, application and research began using various industrial waste and construction material waste of all kinds (waste from tile, marble and granite factories). In this research, we chose two types of waste from tile and granite factories, which we used to stabilize highly plastic soils. The fixation results were good, as the plasticity specifications improved, and the plasticity index became less than 6%. As for the mechanical properties of the soil, it improved significantly when adding each type of waste. The relative endurance properties of the C.B. R for soils with high plasticity increased by seven times when adding 9% granite waste and by 12 times when adding 9% waste from marble and tile factories. The stabilization mechanism proved the improvement of the resistances on the simple pressure of all mixtures and with time from the age of one week to two weeks to four weeks